(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
At first glance, it is not so difficult to distinguish them. Acids have a sour taste and stain indicator paper (litmus paper) red. Basic touches produce a soapy sensation and turn the indicator paper blue. But chemists are not satisfied with such phenomological ones. They are more interested in the question of what causes the molecular structure of a substance to become an acid or a base.